Synthesis and characterization of chromium silicate catalyst and its application in the gas phase glycerol transformation into acetaldehyde - Luizon Filho, Roberto A. [UNESP]; Possato, Luiz G. [UNESP]; Santisteban, Oscar A.N. [UNESP]; de Vasconcellos, Adriano [UNESP]; da Silva, Danilo A. [UNESP]; Lima, Marcelo F. [UNESP]; Martins, Leandro [UNESP]; Nery, José G. [UNESP] (Elsevier, 2020)
Chromium silicates with MFI topology were hydrothermally synthesized, characterized, and applied as heterogeneous catalysts on the one-step gas-phase glycerol conversion into acetaldehyde and acrolein. The catalysts were characterized by XRD, SEM, FT-IR, ICP-OES, XPS, pyridine adsorption, nitrogen adsorption/desorption, and TGA. The experimental results showed that the use of chromium led to a zeolite containing surface-active species and framework chromium atoms, which were identified by XPS analysis, and named as Cr(1), Cr(2) and Cr(3) species. The catalytic reactions with CrMFI-H exhibited high glycerol conversion (97%), and the main products were acetaldehyde (30%) and acrolein (10%). The high yield of acetaldehyde was due to oxidation reactions taking place in Cr(3) species. A reaction pathway for the formation of acetaldehyde was proposed, and the DFT calculations corroborated the proposed mechanism. In comparison with MFI-H catalysts, reactions with CrMFI-H led to the formation or deposition of a negligible amount of coke (less than 3 wt%) either under O2 or N2 atmosphere. This study highlights the advantage of combining acid and redox sites in a single catalyst because the redox sites not only assist the selective conversion of glycerol but also participate in the oxidation of monomeric coke species before they polymerize and block the pores of the catalysts.